Optimization of the Concrete Composition Mix at the Design Stage - Lisienkova, Liubov; Shindina, Tatiana; Orlova, Nina; Komarova, Liudmila (Civil Engineering Journal, 2021)
The problem of the composition optimization of concrete mixes seems to be quite urgent as errors at the composition design stage can lead to problems of concrete at the stage of exploitation such as delamination, cracking etc. Reasonable selection of concrete mix components guarantees the required strength of concrete and reinforced concrete structures in the future. This paper investigates the influence of the concrete mix composition on the strength of concrete. Firstly, typical risks that can occur on the composition design stage have been identified through the experts' interviews. Secondly, this risks were associated with indicators and characteristics that can be tested experimentally. Running of several mathematical models has allowed to outline concrete mix parameters of highest importance and formulate an empirical equation for the dependence of the strength of the concrete mixture on the values of the coarse aggregate quality factor, the fine aggregate fraction and the consumption of the Portland cement has been proposed. As a result, a methodology for controlling the quality of concrete at the stage of the composition design has been formulated.Â Doi: 10.28991/cej-2021-03091732 Full Text: PDF